(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
The article is a continuation and development of the idea of a triadic model of society in relation to a society where money capital is the main thing. The article considers the consequences of the merger of two rights that form the distribution in society in one object – money. Such a merger determines the trajectory of the development of the society of money capital: from the society of industrial production to the society of financial capitalism. The mechanisms of such a transition and its consequences are shown. The issues of the political structure of society arising from the peculiarities of the monetary capital society are considered. In conclusion, questions to the reader are formulated that expand the scope of the article.